2002
DOI: 10.1200/jco.2002.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinase mRNA in Blood of Patients With Melanoma Treated With Adjuvant Interferon

Abstract: Patients with melanoma and tyrosinase mRNA detected in the blood during adjuvant interferon therapy had a worse prognosis compared with patients with undetected tyrosinase mRNA during treatment. Further investigation into the detection of circulating melanoma cells as a surrogate marker of response to adjuvant interferon therapy is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 24 publications
(10 reference statements)
5
42
0
1
Order By: Relevance
“…Moreover, the majority of them developed evidence of circulating melanoma cells during follow-up, whereas only 13 (12%) had positive baseline determinations. Mellado et al (2002) reported similar results in a cohort of 50 stage III patients treated with adjuvant IFN, showing positive results in 12% before treatment and 46% during follow-up. On the other hand, Gogas et al (2002) found a higher percentage of positive results before treatment (50%) in 60 stage IIB -III disease-free patients.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Moreover, the majority of them developed evidence of circulating melanoma cells during follow-up, whereas only 13 (12%) had positive baseline determinations. Mellado et al (2002) reported similar results in a cohort of 50 stage III patients treated with adjuvant IFN, showing positive results in 12% before treatment and 46% during follow-up. On the other hand, Gogas et al (2002) found a higher percentage of positive results before treatment (50%) in 60 stage IIB -III disease-free patients.…”
Section: Discussionsupporting
confidence: 58%
“…It is not conceivable to associate a metastatic spreading with a positive tyrosinase finding detected more than 1 year before, as all the relapses in positive patients from our series occurred within 6 months from the last positive determination. The conversion from a positive to one or more negative determinations during follow-up could be a consequence of adjuvant treatment, as suggested by Mellado et al (2002). Also in our experience, all the positive patients not yet relapsed became negative while under adjuvant treatment.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…67,68 Patients with circulating tumor cells have been shown to have inferior survival, 69 but some investigators have found that circulating melanoma cells add little prognostic value beyond that defined by disease stage. 70 If present in circulation, the tumor cells are usually in extremely minute concentrations.…”
Section: Future Directionsmentioning
confidence: 99%
“…The detection of circulating melanoma cell has been proposed as a sensitive method for selecting patients who are in a high risk to relapse. 1,2 However, after the original description of molecular monitoring of circulating melanoma cells by reverse transcriptase-PCR (RT-PCR) had been published, 3 inconsistent data on sensitivity and clinical relevance of this method have been reported [4][5][6][7][8][9][10][11][12][13][14][15] . Two possible reasons for the conflicting results may exist: (a) a single marker detection, (b) conventional or semiquantitative RT-PCR assay.…”
Section: Introductionmentioning
confidence: 99%